2011
DOI: 10.1021/ja201760c
|View full text |Cite
|
Sign up to set email alerts
|

Ph2P(BH3)Li: From Ditopicity to Dual Reactivity

Abstract: A multinuclear NMR study shows that the deprotonation of diphenylphosphine-borane by n-BuLi in THF leads to a disolvated lithium phosphido-borane Ph(2)P(BH(3))Li of which Li(+) is connected to the hydrides on the boron and two THF molecules rather than to the phosphorus. This entity behaves as both a phosphination and a reducing agent, depending on the kinetic or thermodynamic control imposed to the reaction medium. Density functional theory computations show that H(2)P(BH(3))Li exhibits a ditopic character (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The structural investigations of the two dilithiated phosphido‐borane Li 2 [RP⋅BH 3 ] freshly prepared above were conducted on the basis of the lithium NMR data with the aim of locating the two lithium cations. Note that, in the following, 7 Li NMR is used by default, but we also resorted to 6 Li NMR (deprotonating the phosphine‐boranes with 6 Li‐labeled n BuLi) to either strengthen the conclusion derived from the observations by means of 7 Li NMR or reduce the possibility of peak overlapping…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural investigations of the two dilithiated phosphido‐borane Li 2 [RP⋅BH 3 ] freshly prepared above were conducted on the basis of the lithium NMR data with the aim of locating the two lithium cations. Note that, in the following, 7 Li NMR is used by default, but we also resorted to 6 Li NMR (deprotonating the phosphine‐boranes with 6 Li‐labeled n BuLi) to either strengthen the conclusion derived from the observations by means of 7 Li NMR or reduce the possibility of peak overlapping…”
Section: Methodsmentioning
confidence: 99%
“…Previous work on the structure of a secondary lithium phosphido‐borane (Li[Ph 2 P⋅BH 3 ]) showed that the lithium atom is exclusively next to the borane group. This has led to substantiating the dual reactivity observed for such species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1 H DOSY experiment,, associated with a diffusion coefficient–formula weight correlation analysis in the presence of three internal references (squalene, triphenylbenzene and hexamethyldisilane), was next undertaken. Unfortunately, the two proton signals at −1.00 ppm (monomer) and −1.07 ppm (oligomer 2 or 3 ) are too close to give two different diffusion coefficient values (pages 15S–16S in Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…In 2011, Oulyadi et al [45] proposed the first structural study in solution by multi-NMR ( 1 H, 6 Li, 11 B, 13 C) of lithium phosphido-borane (Scheme 4.2), performed in relation to a mechanistic study on the coupling reaction between the secondary borane phosphines and aryl halides. The data collected by multi-NMR analyses ( 1 H, 6 Li, 11 B, 13 C) are in favor of a preferential interaction of lithium with hydrides rather than with phosphorus.…”
Section: Structure Of a Lithium Phosphido-boranementioning
confidence: 99%